Enhancement of microbial fuel cell anode through functionalization of conductive polymer / Kang Yee Li - Kang , Yee Li (2016)
The incompetency in handling energy and water leads to detrimental consequences to the environment. Hence, sustainable solutions to overcome this situation are crucial for the survival and conservation of ecosystem for the future generation. In recent years, Microbial Fuel Cell (MFC) emerged as the most promising technology that sustainably integrates energy generation and environmental clean-up. Though MFC research was prominent among the academics, it had numerous restrictions that need to be surpassed for real-time feasibility. Most of these are attributed to its components such as anode, biocatalyst and membrane. Hence, the present thesis focused on addressing one of its major limitation, the anode component. The objective of the present research is to develop an enhanced anode for MFC operation. Two different aspects were targeted namely the structural configurations and functionalization of anode with conductive polymer. Different configurations such as plate, cloth and felt were utilized to investigate the influence of geometry and morphology on anode performance. The second part perceive the applicability of a conductive polymer, poly(3,4-ethylenedioxythiophene) (PEDOT) as anode enhancer. The synthesized anodes were then applied onto dual chamber MFC reactor. The optimizations of PEDOT loading onto the three different configurations were evaluated through electrochemical characteristics, system performance and efficiency of these anodes. Subsequently, the biofilm, which governs the production and transfer of electrons in the system, were characterized to genetically identify the microbial genera that are responsible for electricity generation. The biodiversity between the different anodes were investigated and compared to evaluate the influence of PEDOT on biofilm selection and electron transfer mechanism that stimulate the MFC operation. The optimal anodes were then applied to real wastewater as substrate to assess the capability of the systems to utilize complex organic molecule. The felt configuration, which is three-dimensional (3D) and has an open structure, achieved promising results compared to the plate and cloth anodes. The power density of GF anode is 0.52 W/m2 while GP and CC recorded 0.16 W/m2 and 0.35 W/m2 respectively. GF also recorded better coulombic efficiency of 45.4% compared to both GP and CC which only achieved 39% and 31% correspondingly. The incorporation of PEDOT onto the anodes of varied configurations improved the electrochemical characteristics and their performance significantly. The present study also inferred that each anode configurations have different optimum PEDOT loading and peak performances. Among the PEDOT functionalized anodes, GF-P attained the highest power density of 1.62 W/m2 while CC-2P is the most efficient with 58.2% of total electron converted into electricity. The molecular biology analyses were carried for stable biofilms and Geobacter was found to be the dominant genera responsible for the electron production. The study was similarly successful when adopting real wastewater as a substrate. The generated electricity and COD removal by the modified anodes proved its capability in utilizing complex organic waste effectively. Thus, the synergy between optimum structural configuration and PEDOT loading is essential to attain an ideal anode with improved electrochemical characteristics as well as peak voltage generation as discussed in this present study.